The Spread of Tuberculosis Cases in the Highlands and Coastal Areas of Padang - Sidiq, Rapitos; Dewata, Indang; Heldi, Heldi; Syah, Nurhasan; Handayuni, Linda; Asyary, Al (Kesmas, 2025)
The current tuberculosis (TB) worldwide situation is very concerning in terms of the number of cases and the death toll, as well as the environmental factors that contribute to its transmission. This has driven policy decisions that aim to enhance contemporary TB control efforts. This study aimed to map the pattern of TB spread based on geographic location, particularly in the highland and coastal areas of Padang City, West Sumatra Province, Indonesia. This study employed a quantitative descriptive analysis using secondary data from 6 primary health care (PHC) from April 2022 to March 2023, comprising 896 cases. Data analysis was conducted using the ArcGIS program, as well as applying Nearest Neighbor Analysis across the PHC areas. The results indicated that TB cases were more prevalent in coastal areas. The distribution pattern was comparable between the mountainous and coastal areas, as indicated by similar clusters. Geographic differences did not affect the TB transmission pattern in Padang City. The reason for the occurrence of transmission was likely due to close contact, spreading from one person to another. Therefore, more effective education efforts, case detection, and restriction of TB patient movement are necessary to address the issue of interest.